Population biology of uca maracoani latreille 1802-1803 (crustacea, brachyura, ocypodidae) on the south-eastern coast of brazil - Hirose, Gustavo L.; Negreiros-Fransozo, Maria Lucia [UNESP] (My University, 2008)
The population biology of Uca maracoani was investigated in an estuarine mudflat in the Jabaquara River, Paraty, Brazil. The following aspects of this population were analyzed: spatial distribution, body size, size-frequency distribution, sex ratio, recruitment of juveniles, and reproductive period. The population structure presented as a very dynamic population. The median carapace width of males (32.0 mm) was significantly larger than that of females (28.6 mm) (p <0.05). Males predominated during most of the year, except in July and August when the proportion of females was higher. The major pulse of recruitment occurred during winter and spring, probably as a consequence of high reproductive activity in the autumn and winter. Such information is important for conservation of this species, because it is becoming uncommon along the northern coast of the state of São Paulo, near the studied site, in south-eastern Brazil.
Keywords: Population structure; Recruitment; Reproductive period; Sex-ratio; Spatial distribution